DNA templates with blocked long 3ʹ end single-stranded overhangs (BL3SSO) promote bona fide Cas9-stimulated homology-directed repair of long transgenes into endogenous gene loci. Issue 8 (14th May 2021) - Bandyopadhyay, Saptaparni; Douglass, Joseph; Kapell, Sebastian; Khan, Nazimuddin; Feitosa-Suntheimer, Fabiana; Klein, Jenny A; Temple, Jasmine; Brown-Culbertson, Jayce; Tavares, Alexander H; Saeed, Mohsan; Lau, Nelson C
Abstract: Knock-in of large transgenes by Cas9-mediated homology-directed repair (HDR) is an extremely inefficient process. Although the use of single-stranded oligonucleotides (ssODN) as an HDR donor has improved the integration of smaller transgenes, they do not support efficient insertion of large DNA sequences. In an effort to gain insights into the mechanism(s) governing the HDR-mediated integration of larger transgenes and to improve the technology, we conducted knock-in experiments targeting the human EMX1 locus and applied rigorous genomic PCR analyses in the human HEK293 cell line. This exercise revealed an unexpected molecular complication arising from the transgene HDR being initiated at the single homology arm and the subsequent genomic integration of plasmid backbone sequences. To pivot around this problem, we devised a novel PCR-constructed template containing blocked long 3' single-stranded overhangs (BL3SSO) that greatly improved the efficiency of bona fide Cas9-stimulated HDR at the EMX1 locus. We further refined BL3SSO technology and successfully used it to insert GFP transgenes into two important interferon-stimulated genes (ISGs) loci, Viperin / RSAD2, and ISG15 . This study demonstrates the utility of the BL3SSO platform for inserting long DNA sequences into both constitutive and inducible endogenous loci to generate novel human cell lines for the study of important biological processes.